2011
DOI: 10.2174/187152111795508315
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Immune-Mediated Inflammation in Rheumatoid Arthritis Dictates that Development of Anti-Rheumatic Disease Drugs Target Multiple Intracellular Signaling Pathways

Abstract: A skewed repertoire of pro-inflammatory cytokines produced by the T h 1 subset, one of the hallmarks of rheumatoid arthritis (RA), is characterized by an overabundance of pro-inflammatory cytokines. Tumor necrosis factor-, interleukin-1 (IL-1), IL-6, IL-7, IL-8, IL-21, IL-12/IL-23, IL-15, IL-17, IL-18, IL-32, and interferon-are primarily responsible for immune-mediated inflammation of RA by activating Janus kinases (JAK) -1, -2, -3, p38 kinase, C-Jun-Nterminal kinase, extracellular signal-regulated kinase 1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…In light of this contention, we recently suggested that dysfunctional intracellular signaling involving protein kinase pathways other than JAK/STAT as well as “cross-talk” between JAK/STAT and the stress-activated protein kinase/mitogen-activated protein kinase (SAPK/ MAPK) and Phosphatidylinositide-3-Kinase/AKT/mammalian Target of Rapamycin (PI-3K/AKT/mTOR) pathways is likely be required to completely dampen immune-mediated Inflammation and cartilage destruction in RA [26-28]. Supporting this viewpoint are the results of an analysis involving the therapy of active RA with the anti-IL-6 receptor inhibitor, tocilizumab [29].…”
Section: Personalized Molecular Medicinementioning
confidence: 99%
“…In light of this contention, we recently suggested that dysfunctional intracellular signaling involving protein kinase pathways other than JAK/STAT as well as “cross-talk” between JAK/STAT and the stress-activated protein kinase/mitogen-activated protein kinase (SAPK/ MAPK) and Phosphatidylinositide-3-Kinase/AKT/mammalian Target of Rapamycin (PI-3K/AKT/mTOR) pathways is likely be required to completely dampen immune-mediated Inflammation and cartilage destruction in RA [26-28]. Supporting this viewpoint are the results of an analysis involving the therapy of active RA with the anti-IL-6 receptor inhibitor, tocilizumab [29].…”
Section: Personalized Molecular Medicinementioning
confidence: 99%
“…Since we did not determine the extent to which MSU altered NO levels in the normal juvenile chondrocyte pellet cultures, it remains to be determined if the MSU-mediated increase in TUNEL-positive chondrocytes also involved NO. This may prove to be critical because NO is also a potent inducer of chondrocyte apoptosis [1,10,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the appropriate levels and biological activity of circulating T-regulatory (T reg ) cells are required for maintaining immune tolerance [48]. In that regard, Xiao et al [49] showed that T reg cells recovered from RA patients exhibited an impaired capacity to limit the proliferation and cytokine production of autologous T-effector cells which appeared to be due to an intrinsic defect in RA T reg cells .…”
Section: Trailmentioning
confidence: 99%